Effects of operating a solar air heater on the indoor air quality in classrooms during the winter : a case study of Palmerston North primary schools : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Building Technology at Massey University, Auckland, New Zealand - Wang, Yu (Massey University, 2020)
Schools are densely populated places, where children spend a large amount of their time. The indoor air quality (IAQ) in classrooms impacts students’ health, academic outcomes and school absences (Borras-Santos et al., 2013; Mi et al., 2006; Shendell, Prill, et al., 2004; Smedje and Norbäck, 2000; Taskinen et al., 2007). Three New Zealand (NZ) studies have found low ventilation rates, low temperature levels, high relative humidity (RH) levels and high carbon dioxide (CO2) levels during the winter months in NZ primary schools (Bassett and Gibson, 1999; Cutler-Welsh, 2006; McIntosh, 2011). These results show a need to improve the indoor environment in NZ schools during the winter. NZ school hours, from 9 am to 3 pm, are well aligned with the optimum solar radiation and classrooms lend themselves to heat from solar energy. A project was undertaken to investigate if operating a roof-mounted solar air heater (SAH) could improve the classroom IAQ during the winter. This two-year crossover project was undertaken in four Palmerston North (PN), NZ primary schools in 2013 and six PN, NZ primary schools in 2014. These consisted of the four schools participated in 2013 plus two additional schools. In each school, two adjacent classrooms with similar construction characteristics and population characteristics participated in this project. The two adjacent classrooms were randomly assigned either to a treatment group (SAH installed and operated) or to a control group (SAH installed but not operated). The main objective of this project was to investigate the change in levels of the classroom temperature, RH, CO2, and ventilation rate from when a roof-mounted SAH was operating (treatment) and was not operating (control). Resulting from operating the roof-mounted SAH, the temperature in treatment classrooms was on average 0.5 °C higher than in the control classrooms, when both the control and treatment classrooms had the same heater use. When the control and treatment classrooms achieved the same temperature, the heater use in the treatment classrooms was 27% less than the heater use in the control classrooms. Across all schools, CO2 levels in the treatment classrooms were on average 96 ppm lower than in the control classrooms. In five out of 10 schools (50%), the levels of CO2 in the treatment classrooms were lower than in the control classrooms. Only in one treatment classroom did the ventilation rate meet the NZ Ministry of Education recommended level of 4 air changes per hour. Overall, operating a roof-mounted SAH played a positive role in increasing the temperature and ventilation rate in classrooms during the winter. However, there was not sufficient airflow to satisfy the ventilation requirements. Future research should investigate the impact of operating a SAH on the school ventilation and temperature considering increasing the SAH outlet air volumetric flow rate and keeping the outlet air temperature around 18 °C to bring more heated air into classrooms.
Keywords: School buildings; Heating and ventilation; Air quality management; New Zealand; Solar space heating; 401102 Environmentally sustainable engineering